Characterization of LDD-2633 as a Novel RET Kinase Inhibitor with Anti-Tumor Effects in Thyroid Cancer - Hyo Jeong Lee; Pyeonghwa Jeong; Yeongyu Moon; Jungil Choi; Jeong Doo Heo; Yong-Chul Kim; Sun-Young Han (MDPI AG, 2021)
Rearranged during transfection (RET), a receptor tyrosine kinase, is activated by glial cell line-derived neurotrophic factor family ligands. Chromosomal rearrangement or point mutations in RET are observed in patients with papillary thyroid and medullary thyroid carcinomas. Oncogenic alteration of RET results in constitutive activation of RET activity. Therefore, inhibiting RET activity has become a target in thyroid cancer therapy. Here, the anti-tumor activity of a novel RET inhibitor was characterized in medullary thyroid carcinoma cells. The indirubin derivative LDD-2633 was tested for RET kinase inhibitory activity. In vitro, LDD-2633 showed potent inhibition of RET kinase activity, with an IC50 of 4.42 nM. The growth of TT thyroid carcinoma cells harboring an RET mutation was suppressed by LDD-2633 treatment via the proliferation suppression and the induction of apoptosis. The effects of LDD-2633 on the RET signaling pathway were examined; LDD-2633 inhibited the phosphorylation of the RET protein and the downstream molecules Shc and ERK1/2. Oral administration of 20 or 40 mg/kg of LDD-2633 induced dose-dependent suppression of TT cell xenograft tumor growth. The in vivo and in vitro experimental results supported the potential use of LDD-2633 as an anticancer drug for thyroid cancers.